Pemberdayaan Masyarakat Melalui Pengolahan Sampah Organik Menjadi Produk Eco Enzyme Pada Kelompok PKK Desa Gitik - Zaki Al Mubarok (Institut Teknologi dan Bisnis Semarang, 2023)
Community service (PKM) is one of the concrete forms of higher education tridharma. This PKM activity was proposed on the basis of the lack of optimal utilization of organic waste. This service activity is carried out with the aim of empowering the community through processing organic waste into eco enzyme products in the Gitik Village PKK group. The method used is a participatory method, the implementation is carried out in several stages including, namely, material preparation, learning preparation, methods and learning and the results of processing organic waste into eco enzyme products. The results of the dedication show that the training activities have been able to perfectly improve the knowledge and skills of the community in processing organic waste into eco enzymes.